2013
DOI: 10.4304/jnw.8.10.2406-2413
|View full text |Cite
|
Sign up to set email alerts
|

Routing Protocol Design and Performance Optimization in Cognitive Radio Networks

Abstract: Routing protocol is an important issue in cognitive radio networks. This paper explored the issues and challenges of routing protocol in cognitive radio network from five aspects: hidden terminal, exposed terminal, deafness, cross-layer design, and topology. The existed protocols are classified by the metrics: the establishment of active routing, cross-layer routing, and network performance indicators. Focusing on analyzing performance of routing protocols and design optimized schemes in cognitive radio networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Huang et al [15] defined highest, medium and lowest spectrum temperature routing metrics based on primary user presence over a link and showed that their protocol establishes a coolest path. In [16], Wu et al presented performance comparison of existing routing protocols in CRAHNs and discussed on minimizing switching delays, improving route maintenance time, improving routing metric and improving throughput.…”
Section: Related Workmentioning
confidence: 99%
“…Huang et al [15] defined highest, medium and lowest spectrum temperature routing metrics based on primary user presence over a link and showed that their protocol establishes a coolest path. In [16], Wu et al presented performance comparison of existing routing protocols in CRAHNs and discussed on minimizing switching delays, improving route maintenance time, improving routing metric and improving throughput.…”
Section: Related Workmentioning
confidence: 99%